Weldability of an iron meteorite by Friction Stir Spot Welding: A contribution to in-space manufacturing. (November 2017) - Evans, William Todd; Neely, Kelsay E.; Strauss, Alvin M.; Cook, George E.
Abstract: Friction Stir Welding has been proposed as an efficient and appropriate method for in space welding. It has the potential to serve as a viable option for assembling large scale space structures. These large structures will require the use of natural in space materials such as those available from iron meteorites. Impurities present in most iron meteorites limit its ability to be welded by other space welding techniques such as electron beam laser welding. This study investigates the ability to weld pieces of in situ Campo del Cielo meteorites by Friction Stir Spot Welding. Due to the rarity of the material, low carbon steel was used as a model material to determine welding parameters. Welded samples of low carbon steel, invar, and Campo del Cielo meteorite were compared and found to behave in similar ways. This study shows that meteorites can be Friction Stir Spot Welded and that they exhibit properties analogous to that of FSSW low carbon steel welds. Thus, iron meteorites can be regarded as another viable option for in-space or Martian construction. Highlights: Successfully welded low carbon steel, invar and meteoritic material by FSSW. FSSW parameters used for low carbon steel can be applied to meteorite welds. SEM analysis of meteorite weld showed homogeneity and thorough mixing of inclusions. Friction Stir processes are a viable candidate for in situ space welding. Further research should be continued with the FSW process to build on FSSW work.